Victim or actors: the typology of Indonesian woman journalists - Ashaf, Abdul Firman; Kartika, Tina (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper aims to present a typology of woman journalists in media organizations. It utilizes qualitative research method based on in depth interviews with a number of women journalists in the Province of Lampung. Generally, journalist profession is regarded as a man’s world. The nature of work in journalism is considered a competition, especially perceived by male journalists. Equality of rights and obligations is also given a positive value by journalists. Likewise, the appreciation of the voice of women in determining institutional policies is a concrete form of institutional recognition of women's own presence. In the context of gender relations, women journalists reported experiencing the patriarchal environment in which they work in. So much so, that even some women journalists adopted patriarchal values at work. In the context of democratization of gender-based media, the typology of women journalists makes it possible for activism efforts. Literatures also reported low participation of women in media institutions, discriminative patterns of relationships, patriarchal environment, low gender awareness as well as gender-sensitive journalistic work. The study found that female journalists are divided into two typologies, which are: hegemonised women journalists and women journalists as actors of resistance. Hegemony and resistance occur at three levels: gender awareness, media institutions and media routine, as well as context of extra media and patriarchal ideology.